Landscapes of power : politics of energy in the Navajo nation - Powell, Dana E., 1973- (New ecologies for the twenty-first century., 2018)
In Landscapes of Power Dana E. Powell examines the rise and fall of the controversial Desert Rock Power Plant initiative in New Mexico to trace the political conflicts surrounding Native sovereignty and contemporary energy development on Navajo (Diné) Nation land. Powell's historical and ethnographic account shows how the coal-fired power plant project's defeat provided the basis for redefining the legacies of colonialism, mineral extraction, and environmentalism. Examining the labor of activists, artists, politicians, elders, technicians, and others, Powell emphasizes the generative potential of Navajo resistance to articulate a vision of autonomy in the face of twenty-first-century colonial conditions. Ultimately, Powell situates local Navajo struggles over energy technology and infrastructure within broader sociocultural life, debates over global climate change, and tribal, federal, and global politics of extraction.